2021
DOI: 10.1126/sciadv.abf0466
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage miR-210 induction and metabolic reprogramming in response to pathogen interaction boost life-threatening inflammation

Abstract: Unbalanced immune responses to pathogens can be life-threatening although the underlying regulatory mechanisms remain unknown. Here, we show a hypoxia-inducible factor 1α–dependent microRNA (miR)–210 up-regulation in monocytes and macrophages upon pathogen interaction. MiR-210 knockout in the hematopoietic lineage or in monocytes/macrophages mitigated the symptoms of endotoxemia, bacteremia, sepsis, and parasitosis, limiting the cytokine storm, organ damage/dysfunction, pathogen spreading, and lethality. Simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 74 publications
0
23
0
Order By: Relevance
“…Beyond pure hypoxic exposure alone, an appreciation is advancing of the mechanistic connections of ISCU specifically with IL-6 ( 41 ), suggesting the importance of hypoxia and IL-6 together in controlling ISCU-dependent pathophenotypes. Thus, in PAECs exposed to a combination of recombinant IL-6/soluble IL-6 receptor (sIL-6R) and hypoxia, BRD2889 reversed the increase in GSTP1 activity and reversed the decrease in ISCU expression (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond pure hypoxic exposure alone, an appreciation is advancing of the mechanistic connections of ISCU specifically with IL-6 ( 41 ), suggesting the importance of hypoxia and IL-6 together in controlling ISCU-dependent pathophenotypes. Thus, in PAECs exposed to a combination of recombinant IL-6/soluble IL-6 receptor (sIL-6R) and hypoxia, BRD2889 reversed the increase in GSTP1 activity and reversed the decrease in ISCU expression (fig.…”
Section: Resultsmentioning
confidence: 99%
“…During sepsis, activation of type 1 immune response leads to the release of abundant cytokines, which is recognized as the common feature of sepsis, known as "cytokine storm" (Virga et al, 2021). Intriguingly, activation of anti-inflammatory type 2 immune response can antagonize proinflammatory type 1 immunity (Verhoef et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction and Western blotting were performed as previously described (Virga et al, 2021). Briefly, the protein sample (30 µg) was electrophoresed in SDS-PAGE and transferred to the PVDF membrane.…”
Section: Protein Extraction and Western Blotting Assaymentioning
confidence: 99%
“…Similarly, HIF-1α is upregulated in SARS-CoV-2 patients and promotes macrophage inflammatory responses ( Zhu et al, 2021a ). HIF-1α can also induce miR-210 to shift macrophages to a proinflammatory state while knocking down miR-210 limits the cytokine storm ( Virga et al, 2021 ). Nevertheless, the complex formation between HIF-1α and PKM2 inhibits the expression of HIF-1α and IL-1β and promotes the expression of IL-10, in turn leading to a shift in the macrophage phenotype from proinflammatory M1 to pro-reparatory M2 ( Palsson-McDermott et al, 2015 ).…”
Section: Glycolysis and Innate Immunitymentioning
confidence: 99%
“…In addition, it was shown by using galactose medium and 2-DG that inhibition of glycolysis can repress HCV from cell to supernatant release ( Yu et al, 2021 ). While glycolysis may contribute to the inflammatory storm ( Wang et al, 2020b ; Virga et al, 2021 ), the absence of glycolysis can lead to the loss of antiviral function in NK cells. Sheppard et al (2021) found that LDHA-mediated aerobic glycolysis is a hallmark of NK cell activation.…”
Section: Glycolysis and Innate Immunitymentioning
confidence: 99%